KALA DALAM BAHASA JEPANG - I Gede Oeinada (Journal Social and Humaniora, 2017)
This paper focuses its discussion about tenses in Japanese language. Di?erent from Indonesian language but similar to English language, the Japanese language also has tenses in its grammar categories. The mastering of this grammar category namely tense in Japanese is an essential element for Japanese language learners so that they can be able to produce accurate Japanese sentences which will never be misunderstood by their listeners or readers. The discussion about tenses in Japanese grammar category in this paper is based on the argument from Harasawa (2010). Keywords : Japanese Grammar Category, Tense, Absolute and Relative Tenses